2002
DOI: 10.1016/s0014-5793(02)02866-1
|View full text |Cite
|
Sign up to set email alerts
|

A role for calcium in sphingosine 1‐phosphate‐induced phospholipase D activity in C2C12 myoblasts

Abstract: Receptor-regulated phospholipase D (PLD) is a key signaling pathway implicated in the control of fundamental biological processes. Here evidence is presented that in addition to protein kinase C (PKC) and Rho GTPases, Ca 2+ response evoked by sphingosine 1-phosphate (S1P) also participates to the enzyme regulation. Ca 2+ was found critical for PKCK K-mediated PLD activation. Moreover, S1P-induced PLD activity resulted diminished by calmodulin inhibitors such as W-7 and CGS9343B implicating its involvement in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Because gap junctions are required for normal myogenesis (Araya et al, 2005), we next investigated whether known mediators of the myogenic program and known targets of S1P, such as Ca 2ϩ and p38 MAPK (Meacci et al, 2002a;Porter et al, 2002;Cabane et al, 2003;Donati et al, 2005), could also play a role in the regulation of Cx43 expression induced by the bioactive lipid. To this end, we used BAPTA/AM (15 M), a calcium chelator capable of preventing intracellular calcium increase, or SB239063 (5 M), a specific inhibitor of p38 MAPK, and focused our observations on the time period where the effect of S1P on protein expression was predominant (48 h).…”
Section: Calcium Increase and P38 Mapk Activity Are Involved In S1p-imentioning
confidence: 99%
“…Because gap junctions are required for normal myogenesis (Araya et al, 2005), we next investigated whether known mediators of the myogenic program and known targets of S1P, such as Ca 2ϩ and p38 MAPK (Meacci et al, 2002a;Porter et al, 2002;Cabane et al, 2003;Donati et al, 2005), could also play a role in the regulation of Cx43 expression induced by the bioactive lipid. To this end, we used BAPTA/AM (15 M), a calcium chelator capable of preventing intracellular calcium increase, or SB239063 (5 M), a specific inhibitor of p38 MAPK, and focused our observations on the time period where the effect of S1P on protein expression was predominant (48 h).…”
Section: Calcium Increase and P38 Mapk Activity Are Involved In S1p-imentioning
confidence: 99%
“…An important sphingolipid metabolite is sphingosine 1-phosphate (S1P), which mainly acts through Gprotein-coupled receptors present on mammalian cells, thereby regulating numerous cell functions, including cell proliferation, differentiation and apoptosis (Zeidan and Hannun, 2007). In the last few years, most of the studies of our group have been focused on the role played in skeletal muscle cell biology by S1P, as a modulator of intracellular Ca 2+ mobilization, phosphatidic acid synthesis and phospholipid remodelling in skeletal muscle cells (Bencini et al, 2003;Donati et al, 2005;Formigli et al, 2002;Meacci et al, 1999;Meacci et al, 2002a;Meacci et al, 2002b). Recently, we have underscored the physiological relevance of the sphingosine-kinase-S1P axis in C2C12 cell growth arrest and differentiation and identified the essential steps of the pro-myogenic action of S1P in skeletal myoblasts, including formation of SFs, upregulation of connexin 43 protein and its interaction with cortical actin (Formigli et al, 2007b;Squecco et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies [24][25][26][27], we demonstrated that in murine C2C12 myoblasts phospholipase D (PLD) is regulated by several agonists, including bradykinin, thrombin and S1P, and the signalling pathways involved were characterized. In the present study, we provide evidence that Sph is capable of activating PLD in C2C12 myoblasts through its phosphorylation to S1P, and that an intrinsic SphK activity, detected in the extracellular compartment, contributes to the observed biological activity.…”
Section: Introductionmentioning
confidence: 99%